Ecological description of the ovarian activity in alpacas (Vicugna pacos) - Pacheco, Joel I. (2017)
Ovarian follicular growth was described in alpaca weaned females maintained on native and cultivated pastures. Fifty-five alpacas of 8 months on average of age were used, divided into two groups, group 1 (cultivated pastures, n = 23) and group 2 (natural pastures, n = 33). Live weight, uterine size and follicular development using ultrasound were recorded every 15 days. At the first evaluation, 43.5% of small follicles were found in group 1 compared to 6.1 of small follicles in females of group 2. Median follicles were present in the two groups at 9 months of age in 9.1 and 30.1% respectively for groups 1 And 2. Large follicles are found in 5.5% of group 1 alpacas at an average age of 11 months and an average weight of 33.9 kg, while in group 2 it was observed that 3.0% of alpacas showed large follicles at an average age of 10.5 months and an average live weight of 28.1 kg. It is evident that in females that presented follicles of the three sizes described, they had a greater live weight than those that did not present ovarian activity. The uterine diameter was not strongly associated with the ovarian follicular activity of the alpacas (P> 0.05).